Metastatic nasopharyngeal carcinoma: Outcome from Cancer Institute, Chennai - Arun Kumar; Harish Kumar; Manikandan Dhanushkodi; Selvaluxmy Ganesharajah (Indian Journal of Medical and Paediatric Oncology)
Background: Optimal management of metastatic nasopharyngeal carcinoma (NPC) at presentation is debatable. The aim of this study was to investigate the treatment outcome of patients with metastatic NPC treated with concurrent chemoradiation or with radiation alone and to analyze the factors that correlate with the outcome. Methods: This was a retrospective study of patients with metastatic NPC treated in Cancer Institute, Chennai, from 1996 to 2015 with either chemoradiation or only radiation. Factors including age, sex, stage, treatment type, and type of metastasis were correlated with the outcome. Statistical analysis was done using SPSS version 20, and survival was estimated by Kaplan–Meier's curve. Results: A total of 515 patients with NPC were treated during this period, and among them, 74 patients (14%) had metastasis at the time of presentation. The median follow-up was 14 months; the median progression-free survival and overall survival (OS) were 11 months and 19 months, respectively. About 72% (n = 53) were treated with chemoradiation and the rest 28% (n = 21) were treated with radiation alone. The 3-year OS was better in patients who received chemoradiation (39%) as compared to those who received only radiation (23.8%). Patients with the bone-only site of metastasis had better survival. Among them patients with oligometastatic bone disease (1–3 sites) had a better 3-year OS (51%) as compared to multiple bone metastasis (>3) 15.8%. Conclusion: Chemoradiation can be an option to treat metastatic NPC. Patients with oligometastatic bone disease had better survival.